Mobile money demand in utility bill payments: A WTP estimate from Ethiopia. Issue 1 (2nd January 2022) - Awel, Yesuf; Yitbarek, Eleni
ABSTRACT: The study assess mobile money demand for utility bill payments and identify factors that affect its adoption in Ethiopia. We use data from urban household survey and dichotomous choice experiment that randomly offer a range of prices for using mobile money to pay utility bills. We find that households are willing to pay a higher price to use mobile money than the actual price charged by current mobile money service providers for the payment of goods and services. However, demand is sensitive to price changes. Our findings suggest strong latent demand for mobile money in processing payments.